Evaluation of Nursing Students' Perceptions of the Phenomenon of Smoking Behavior - Ayu Gustiana; Buenalyn Teresita Ramos-Mortel; Nonthaphat Theerawasttanasiri (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to describe nursing students' perceptions of smoking behavior. Methodology:The research method used in this research is quantitative descriptive research. The research sample was selected using a simple random sampling technique to ensure the representativeness of the samples taken. The sample of respondents in this research was 20 students. The instrument used to collect data was a questionnaire. Analysis of research data was carried out using descriptive statistics, especially using SPSS. Main Findings: Students' perceptions about smoking behavior on the knowledge indicator about the impacts of smoking were found to be in the good category with an average percentage of 75%. Students' perceptions about smoking behavior in the attitude indicator towards smoking behavior were found to be in the good category with an average percentage of 65%. Students' perceptions about smoking behavior on indicators of action plans to prevent or reduce smoking behavior were found to be in the good category with an average percentage of 70%. Novelty/Originality of this study: The novelty of this study lies in its comprehensive approach to nursing students' perceptions, providing valuable insight into how prospective nurses perceive and respond to the phenomenon of smoking behavior.